Social differences in spatial perspectives about local benefits from rehabilitated mangroves: insights from Vietnam. Issue 1 (31st December 2022) - Carrie, Rachael H.; Stringer, Lindsay C.; Van Hue, Le Thi; Quang, Nguyen Hong; Van Tan, Dao; Hackney, Christopher R.; Nga, Pham Thi Thanh; Quinn, Claire H.
ABSTRACT: Change in mangrove extent and condition has potential consequences for social disparity in terms of who can adapt to change in ecosystem services and places perceived important for providing them. Participatory GIS can elicit spatial variation in the importance attached to ecosystem service places, but disaggregated research that can reveal difference over the small spatial extents often covered by mangroves is underdeveloped. Using mixed-methods (quantitative, qualitative and spatial) in a rehabilitated mangrove system in Vietnam, this study assesses if and why perspectives about ecosystem services and their providing places vary among households with different capacities to adapt to mangrove change.Three household groups with different adaptive capacities were characterised using quantitative adaptive capacity indicators, demographic and economic data, and trajectory interviews spanning three decades: accumulating, coping and flexible households Coastal protection was identified as beneficial by all, and sediment, habitat provisioning and food services were also frequently associated with mangroves. Only food was identified significantly more or less by different groups. Spatial hotspots generated for each group by quantifying overlap in places perceived important for providing these four services, revealed greatest difference in locations important for food. Interviews indicated change in the characteristics of mangrove localities and different abilities to adapt to them enabled some households to prosper while others struggled. We consider adaptive capacities that helped temper mangrove change, and who might be most impacted by continuing change. We conclude by identifying ways forward for rehabilitation strategies centred on local people's differential adaptive capacity and multiple ecosystem service needs.